2022
DOI: 10.1128/mbio.00628-22
|View full text |Cite
|
Sign up to set email alerts
|

The Transcription Factor Roc1 Is a Key Regulator of Cellulose Degradation in the Wood-Decaying Mushroom Schizophyllum commune

Abstract: Wood-degrading fungi in the phylum Basidiomycota play a crucial role in nutrient recycling by breaking down all components of wood. Fungi have evolved transcriptional networks that regulate expression of wood-degrading enzymes, allowing them to prioritize one nutrient source over another.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 65 publications
0
25
0
Order By: Relevance
“…We also found that the C. cinerea ortholog (protein ID: 447627) of the S. commune roc1 transcription factor was significantly upregulated in both mutants. Roc1 was recently described as a regulator of cellulase genes in S. commune ( 46 ). Similarly, a heat shock factor-type gene (protein ID: 523533) related to the S. cerevisiae skn7 transcription factor was upregulated in both mutants.…”
Section: Resultsmentioning
confidence: 99%
“…We also found that the C. cinerea ortholog (protein ID: 447627) of the S. commune roc1 transcription factor was significantly upregulated in both mutants. Roc1 was recently described as a regulator of cellulase genes in S. commune ( 46 ). Similarly, a heat shock factor-type gene (protein ID: 523533) related to the S. cerevisiae skn7 transcription factor was upregulated in both mutants.…”
Section: Resultsmentioning
confidence: 99%
“…These transcription factors include ones specifically responsible for the activation of substrate-specific sets of enzyme-encoding PCWDEs, such as xylanases, cellulases, pectinases (Benocci et al, 2017, Thieme et al, 2017, Klaubauf et al, 2014. While several TFs regulating specific PCWDE genes have been described in the Ascomycetes, only a single gene, Roc1 of S. commune (Marian et al, 2021) has been associated with cellulose degradation in the Basidiomycota. Our data revealed several transcription factors that are differentially expressed in C. cinerea cre1 mutants, providing candidates for novel TFs related to plant biomass utilisation.…”
Section: Discussionmentioning
confidence: 99%
“…First, the C. cinerea ortholog of Roc1 ortholog is upregulated in both independent C. cinerea cre1 mutants. The Schizophyllum commune transcription factor gene roc1, which is conserved among Agaricomycetes, was strongly upregulated in the cellulose containing medium and knockouts showed reduced growth on the cellulose medium, demonstrating its importance in regulating cellulose degrading genes (Marian et al, 2021). ChIP-Seq analysis of S. commune Roc1 identified promoters of genes involved in lignocellulose degradation, particularly LPMOs (Marian et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations